THE URGENCY OF IMPLEMENTING PLEA BERGAINING IN THE INDONESIAN CRIMINAL JUSTICE SYSTEM - Kurniawan, Itok Dwi; Budyatmojo, Winarno (Institut Pendidikan Tapanuli Selatan, 2025)
Plea Bargaining is a legal process in which a accused in the process of examining a criminal case voluntarily admits his guilt or is willing to admit his guilt or is willing to admit his guilt or several charges filed by the public prosecutor. This process aims to reach an agreement between the public prosecutor and the accused regarding the confession of sin and the sentence imposed, without going through a complete trial. Plea Bargaining was implemented for the first time in the United States which adheres to the common law legal system. Indonesia, through its KUHAP reform plan, intends to implement plea bargaining, but it has a different concept from that found in the United States. The writing of this article will analyze the concept of Plea Bargaining contained in the reform of the Criminal Procedure Code and the realization of protection for the rights of suspects and accuseds at every stage of the criminal investigation process. This article was written using a normative research method with a conceptual approach. The results of this research are that the application of Plea Bargaining in criminal procedural law in the future will result in fair law enforcement and legal certainty if it pays attention to the rights of suspects and accuseds. The concept of plea bargaining in the draft KUHAP needs to be based on the principle of protecting the rights of suspects and accuseds.